Comparison of the structuring factors in production from cuts generated in the pig waste (Revista Sistemas de Producción Agroecológicos, 2019)
With the intention of generating added value to the cuts of pork originated in the preparation process. Pork leg muscle trimmings were used to make restructured meat. Three factors were taken into account: particle size, binder and firing method. It was defined for the particle size to grind the cutout with a disc of 20 millimeters and cube it with a size of 1cm3. For the binder type the commercial products were selected from a base of carrageenan and a 1.5% calcium alginate and for cooking, there were used cooked methods and roasting. The experimental design chosen was 23 by orthogonal polygons with eight treatments and three replicates. Comparison of Tukey mean (α=0.05) was used to perform the analysis of variance. The results show that there were no significant differences with respect to the cut resistance among the eight treatments evaluated. It was evidenced that the treatment 5 (cubes, alginate, cooked) was the closest to presenting significant differences with a cut resistance of 47.98 N, being the one that most resembled a cut of meat of whole muscle but with an additional characteristic of tenderness that generates added value to the final product.
Keywords: Binders; meat cuts; restructured meat